Effects of water deficit stress and salicylic acid preharvest treatments on postharvest biochemical parameters of potato - Acevedo, Andres Felipe Gaona [UNESP]; Lacerda, Vander Rocha [UNESP]; Avilez, Alberto Mario Arroyo [UNESP]; Silva, Julio Cesar de Almeida [UNESP]; Vieites, Rogerio Lopes [UNESP] (My University, 2025)
Harvest conditions, harvest state and the pre-treatments to which the potato plant is subjected to affect post-harvest quality. The present study was conducted to verify the effect of the SA foliar application challenged with water deficit stress (WDS, 45 kPa) and control (10 kPa). After the harvest process, the tubers of both treatments were treated with a SA solution (8 mM). Tubers were stored in a dark room at temperature (20 ± 3.5 °C) with relative humidity (65 ± 5 RH) for a period of 60 days, evaluated with different biochemical parameters. The results showed that foliar application of SA presented positive effects in the mitigation of oxidative damage through the dismutation of reactive oxygen species (ROS), suggesting the protection of the cellular membrane structure. Furthermore, there was less accumulation of malondialdehyde and synthesis of bioactive compounds, which certainly increased the antioxidative capacity of plants. WDS tuber was the treatment that presented the highest antioxidant activity with 1.82 µM FeSO4 mg−1. In general, the results indicated that the foliar application of SA and immersion with the same acid in post-harvest presented a positive effect in the biochemical parameters.
Keywords: Antioxidant activity; Post-harvest; Salicylic acid; Shelf-life